Archaeology of the river basin Guabayacu, Región San Martín, Perú. - Bueno Mendoza, Alberto (2009)
The territories of Amazonas and San Martin regions are geographically continuous, both the ecosystem and high Andean cloud forest, are characterized by valleys, gorges, canyons, slopes, geomorphology and high volcanic lakes, numerous rivers of vanous pursue higher volumes lowlands, the Huallaga River draining its greatest manifoid. In the San Martin region of a conjunction of the Andean highlands north (province of Bolivar, La Libertad) on the right bank of the Marañon River, whose penetrating extends punas jalcas and the Mount of Clouds. The archaeological surveys and the years 2003-2005 were executed under the auspices of the american explorer Gene Savoy. The archaeological sites discovered are located on both banks of the river Guabayacu, High Saposoa district, province of Huallaga.